IMPLEMENTASI STANDARISASI PENGUKURAN KEBUGARAN JASMANI SEBAGAI UPAYA PEMBINAAN PRESTASI SISWA SSB JUANDA FC SIDOARJO - Nurul Hikam Arifah; Nurul Hikam Arifah, Nurul Hikam Arifah; Niken Larasati; Nararia Kirana Bhakti; Rizal Akbar; Risky Fitrianto; Ramadhan Ali Jafar; Santika Rentika (Universitas PGRI Adi Buana Surabaya, 2025)
This community service activity aims to assist Juanda FC Football School (SSB) in Sidoarjo in developing a structured and valid physical fitness evaluation system. The main issue faced was the absence of a standardized method for measuring physical fitness, resulting in data that lacked accuracy to support the coaching program. The method used was a combination of classical lectures and hands-on training in conducting the Multistage Fitness Test (MFT) and the Harvard Step Test. The activity was conducted over two days and involved 26 participants consisting of coaches and students. The results showed that 33.3% of the students were in the moderate fitness category, 23.8% in the good category, and 9.5% in the very good category. Meanwhile, 14.3% were in the low fitness category, and 19.1% in the very low category. In addition, the coaches' ability to independently carry out valid and reliable fitness tests improved significantly. This activity is expected to establish a culture of data-based evaluation and strengthen early-age athlete development at Juanda FC Football School.